Semitendinosus Tendon Autograft Length and its Correlation with Anthropometric Measurements in Patients Undergoing Arthroscopic Anterior Cruciate Ligament Reconstruction using Hamstring Tendon Autograft in a Tertiary Care Centre - Pradhan, Ishor; Regmi, Subhash; Panthi, Ashish Kumar; Joshi, Amit; Singh, Nagmani; Basukala, Bibek (Nepal Orthopaedic Association Journal, 2023)
Introduction: There is limited data available regarding semitendinosus tendon length and its correlation with anthropometric parameters in Nepalese population. This study aims to find out mean semitendinosus tendon length in patients undergoing arthroscopic anterior cruciate ligament reconstruction and its correlation with patient’s height, femur length, and thigh girth. Methodology: An observational study was conducted following institutional review committee (IRC) approval (reference number: B&BIRC-23-04). All Patients undergoing arthroscopic anterior cruciate ligament reconstruction using hamstring tendon autograft between January 1, 2021, and December 31, 2022, were included. Those who had premature rupture of semitendinosus tendon during graft harvest were excluded. Semitendinosus tendon autograft was harvested, and length was measured. Then, triplicated graft diameter was measured. If harvested gracillis, quadrupled or pentapled, combined semitendinosus and gracilis tendon autograft diameter was measured. Pearson’s correlation coefficient was used to evaluate correlation and student t test was used to test the significance. Results: Out of 102 included patients, 87(85.3%) were male and 15(14.7%) were female. Mean age of the patients was 30.5 ± 8.4 years. Semitendinosus tendon alone autograft was used in 26(25.5%) cases. and combined semitendinosus and gracillis tendon was used in 76(74.5%) cases. Mean semitendinosus tendon autograft length was 27.9±2.8 cm. There was significant positive correlation between semitendinosus tendon autograft length and patients’ height (r= 0.594, p=.000) and femur length (r=0.528, p=.000). Conclusion: Mean semitendinosus tendon autograft length in patients undergoing arthroscopic anterior cruciate ligament reconstruction is comparable to what reported in other international studies. Semitendinosus tendon length is significantly positively correlated with patients’ height and femur length.